2019
DOI: 10.1073/pnas.1911431116
|View full text |Cite
|
Sign up to set email alerts
|

ITPK1 mediates the lipid-independent synthesis of inositol phosphates controlled by metabolism

Abstract: Inositol phosphates (IPs) comprise a network of phosphorylated molecules that play multiple signaling roles in eukaryotes. IPs synthesis is believed to originate with IP3 generated from PIP2 by phospholipase C (PLC). Here, we report that in mammalian cells PLC-generated IPs are rapidly recycled to inositol, and uncover the enzymology behind an alternative “soluble” route to synthesis of IPs. Inositol tetrakisphosphate 1-kinase 1 (ITPK1)—found in Asgard archaea, social amoeba, plants, and animals—phosphorylates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 75 publications
3
86
0
Order By: Relevance
“…This pathway was thought be unique to these organisms, along with land plants. However, a very recent publication by Desfougères et al shows that the Lipid-Independent pathway is also present in mammals [28]. This work is the first to report evidence of the Lipid-Independent pathway in mammals and will be crucial for exploring the evolution of enzymes across organisms.…”
Section: Insp 6 Synthesis: the Lipid-dependent Pathwaymentioning
confidence: 54%
See 2 more Smart Citations
“…This pathway was thought be unique to these organisms, along with land plants. However, a very recent publication by Desfougères et al shows that the Lipid-Independent pathway is also present in mammals [28]. This work is the first to report evidence of the Lipid-Independent pathway in mammals and will be crucial for exploring the evolution of enzymes across organisms.…”
Section: Insp 6 Synthesis: the Lipid-dependent Pathwaymentioning
confidence: 54%
“…Although more work needs to be done, this suggests that animals may also utilize ITPKs in a Lipid-Independent InsP 6 pathway. In the same work, these authors also found that the plant ITPK1 could complement the yeast PLC mutant, suggesting that the plant ITPK may also have a very flexible substrate preference, and may act at several different steps in the Lipid-Independent pathway [28].…”
Section: Insp 6 Synthesis: the Lipid-independent Pathwaymentioning
confidence: 82%
See 1 more Smart Citation
“…IP6 research is divided into two major areas: studying the role of intracellular IP6 (Int-IP6) by manipulating the enzymes that synthesize or metabolize this molecule, and assessing the impact of dietary supplementation of IP6 (Sup-IP6) in health. Besides the already established PIP2 or IP3 [8,12,14,18,20,[23][24][25][26][27], glucose-6-phosphate and sphingolipids can also be precursors of Int-IP6 [23]. Int-IP6 regulates many cellular functions including stress responses, development, phosphate homeostasis, DNA repair, RNA editing, mRNA export and post-translational modification [94,95,189].…”
Section: Role Of the Ip6k Substrate Ip6 In Metabolismmentioning
confidence: 99%
“…In addition to the classic lipid-IP3 pathway (phosphatidylinositol 4,5-bisphosphate, PIP2 is cleaved to diacylglycerol and inositol 1,4,5-trisphosphate IP3. IP3 gets converted to higher IPs and IPPs), a soluble route also exists where conversion of the glucose-6-phosphate to IP1 serves as a precursor of higher IPs and IPPs [23]. Additional details of IPPs, their metabolizing enzymes, functions and mechanism of actions have been reviewed ( [8,12,14,18,20,[23][24][25][26][27][28] and references therein).…”
Section: Introductionmentioning
confidence: 99%